Event-by-event fluctuations of transverse momentum and multiparticle clusters in relativistic heavy-ion collisions - Florkowski, W. (2007)
We analyze the event-by-event fluctuations of mean transverse momentum measured recently by the PHENIX and STAR Collaborations at RHIC.We argue that the observed scaling of strength of dynamical fluctuations with the inverse number of particles can be naturally explained by formation of multiparticle clusters.